2015
DOI: 10.3109/10253890.2015.1038992
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maternal care is associated with DNA methylation of the genes for brain-derived neurotrophic factor (BDNF) and oxytocin receptor (OXTR) in peripheral blood cells in adult men and women

Abstract: In adults, reporting low and high maternal care in childhood, we compared DNA methylation in two stress-associated genes (two target sequences in the oxytocin receptor gene, OXTR; one in the brain-derived neurotrophic factor gene, BDNF) in peripheral whole blood, in a cross-sectional study (University of Basel, Switzerland) during 2007-2008. We recruited 89 participants scoring < 27 (n = 47, 36 women) or > 33 (n = 42, 35 women) on the maternal care subscale of the Parental Bonding Instrument (PBI) at a previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
125
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(137 citation statements)
references
References 68 publications
8
125
3
1
Order By: Relevance
“…Furthermore, we found that exposure to acute psychosocial stress was associated with a short-term increase in OXTR methylation, followed by a decrease during the stress recovery period (Unternaehrer et al, 2012). Finally, adults reporting low maternal care during childhood had elevated levels of DNA methylation in one of two examined OXTR target sequences (Unternaehrer et al, 2015).…”
Section: Introductionmentioning
confidence: 74%
“…Furthermore, we found that exposure to acute psychosocial stress was associated with a short-term increase in OXTR methylation, followed by a decrease during the stress recovery period (Unternaehrer et al, 2012). Finally, adults reporting low maternal care during childhood had elevated levels of DNA methylation in one of two examined OXTR target sequences (Unternaehrer et al, 2015).…”
Section: Introductionmentioning
confidence: 74%
“…Moreover, there was a significant main effect of rs53576 genotype on OXTR exon 2 methylation – women carrying the A allele had significantly higher methylation status than GG homozygous individuals. Importantly, there is evidence that early maternal care is associated with differential methylation of regions in the OXTR gene of adults (Unternaehrer et al, 2015). In one target sequence positioned at exon 3 of the OXTR gene, there was a negative association between maternal care and blood-derived OXTR DNA-methylation levels.…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 99%
“…DNA methylation of the OXTR gene may be moderated by environmental contingencies, like poor maternal care in childhood (Beery et al, 2015; Unternaehrer et al, 2015), and genotype (Bell et al, 2015). However, comparability between studies is difficult because they differ greatly in target sequences and partly show effects that are not in the expected direction.…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 99%
“…In humans, poor maternal care provision has also been associated with altered DNA methylation. Increased methylation of the BDNF and oxytocin receptor genes in whole blood has been observed in adults who report low maternal care provision during the first 16 years of life [78]. Notably, changes in DNA methylation were only observed in some regions of these genes but not others, indicating a specific DNA methylation response to this exposure.…”
Section: Dna Methylation Biomarkers Of Neurodevelopment Outcomementioning
confidence: 99%